Employee's perception towards management transparency: a case study at Kota Kinabalu City Hall (DBKK) / Noor Razilah Abd Rahman - Abd Rahman, Noor Razilah (2011)
This research focuses on the factors that associated with employees' perception towards management transparency at Kota Kinabalu City Hall. The views and perceptions of employees of the Kota Kinabalu City Hall are presented in the form of data gathered through questionnaires. Factors concerns are on the communication, trust, and leadership in the organization particularly the City Hall. This study will analyze the management transparency at the workplace as the employees perceived. The findings show that communication, trust and leadership are associated with the employees' perception towards management transparency at Kota Kinabalu City Hall. Results from the research were expected to contribute new information in the development criteria and things need to be concerned of any changes within public agency.